Haciendo la transición hacia atención en centros : evaluación del impacto de los centros de desarrollo infantil (2014)
Video recomendado: https://www.youtube.com/watch?v=qfJ7GIQiCVo&index=5&list=PL7vYTBjTHAqSLB6ogHKqDSah08C1M7gvD